2020
DOI: 10.3389/fmicb.2020.523142
|View full text |Cite
|
Sign up to set email alerts
|

Nodule and Root Zone Microbiota of Salt-Tolerant Wild Soybean in Coastal Sand and Saline-Alkali Soil

Abstract: Soil salinization limits crop growth and yield in agro-ecosystems worldwide by reducing soil health and altering the structure of microbial communities. Salt-tolerant plant growthpromoting rhizobacteria (PGPR) alleviate plant salinity stress. Wild soybean (Glycine soja Sieb. and Zucc.) is unique in agricultural ecosystems owing to its ability to grow in salinealkali soils and fix atmospheric nitrogen via symbiotic interactions with diverse soil microbes. However, this rhizosphere microbiome and the nodule endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…More than 800 Mha of the world's agricultural land is composed of saline soil, either based on salinity (397 Mha) or sodicity (434 Mha) (FAO, 2020), whereas there is approximately 8.11 × 10 7 ha of saline-alkali soil in China, which accounts for 8%-9% of the total land area (Zhao et al, 2014). The Yellow River delta is one of the three largest river deltas in China and is becoming an important region for agricultural development (Jing et al, 2019); however, crop production is limited by high soil salinity (Yang et al, 2020), and thus far, the utilization of this saline-alkali land has not been effectively managed. The development of strategies to make use of saline-alkali land will be crucial in addressing problems of insufficient cropland and meeting the challenge of providing food security for the projected global population of 9.3 billion people by 2050 (Shabala et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…More than 800 Mha of the world's agricultural land is composed of saline soil, either based on salinity (397 Mha) or sodicity (434 Mha) (FAO, 2020), whereas there is approximately 8.11 × 10 7 ha of saline-alkali soil in China, which accounts for 8%-9% of the total land area (Zhao et al, 2014). The Yellow River delta is one of the three largest river deltas in China and is becoming an important region for agricultural development (Jing et al, 2019); however, crop production is limited by high soil salinity (Yang et al, 2020), and thus far, the utilization of this saline-alkali land has not been effectively managed. The development of strategies to make use of saline-alkali land will be crucial in addressing problems of insufficient cropland and meeting the challenge of providing food security for the projected global population of 9.3 billion people by 2050 (Shabala et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…[9,71,78]. Moreover, among the same studies, high abundances of Chloroflexi were observed in the rhizosphere of soybean, oilseed rape, and wild grassland species [9,72,78], and-together with Flavisolibacter-even in the microbial community in the nodules of wild soybean [76]. OTUs assigned to the ammonia-oxidizing archaea Candidatus Nitrososphaera [81,82] were reported from the rhizosphere of oilseed rape and maize, and Rhizobium from the endosphere of oilseed rape, wheat, and canola roots [78,79].…”
Section: Dominant Taxa In Rhizosphere Versus Endospherementioning
confidence: 69%
“…Gemmatimonadetes were among the four dominant phyla in the rhizosphere of lentil, pea, soybean, wheat, maize, canola, oilseed rape, artichoke, and diverse grassland species from temperate zones in Europe or the Chinese tundra [9,26,72,[76][77][78][79][80]. Several of these studies demonstrated the enrichment of Gemmatimonadetes in the rhizosphere as compared to bulk soil [78] and linked this phylum to increased biomass production or increased resistance to salt stress [76,77,80], mainly due to abundant nitrogen-fixing Gemmatimonas spp. [9,71,78].…”
Section: Dominant Taxa In Rhizosphere Versus Endospherementioning
confidence: 99%
“…Owing to complex geographic and ecological conditions, there are many genotypes of wild soybean distributed throughout China following long-term climatic and environmental selection ( Guo et al, 2012 ; Li and Wang, 2020 ). Current studies have concentrated on the microbiome of root nodules ( Yang et al, 2020 ; Zheng et al, 2020 ) and the rhizosphere ( Chang et al, 2019 ; Tian et al, 2020 ) to investigate the microbial nitrogen fixation capacity in this legume species ( Mahmud et al, 2020 ). However, little information has been reported on the importance of climate and host genotype in regulating the foliar microbiome of wild soybeans.…”
Section: Introductionmentioning
confidence: 99%